2015
DOI: 10.1039/c5cp01055a
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation dynamics of deeply supercooled confined water in l,l-diphenylalanine micro/nanotubes

Abstract: The temperature dependence (10 − 290 K) of the low-frequency (20 − 150 cm −1 ) Raman-active phonon modes of supercooled confined water in L,L-diphenylalanine micro/nanotubes was analysed. The isolated dynamics of a specific geometry of water cluster (pentamer) in supercooled confined regime was studied in detail. A particular mode concerning water-nanotube interaction was also probed. A fragile-to-strong transition at 204 K was observed and related to the crossing of the Widom line. The critical exponent analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Water can be rapidly supercooled to -43 degC (230 degK)the upper limit to superconducting Tc according to the present theoryor lower by confining water at nanoscale, e.g. in nanotubes 13. Recent x-ray studies of water supercooled to -15 degC in a quartz capillary have revealed the presence of pentagonal dodecahedral and other pentagonal water clathrate nanoclusters similar to those shown in Figs.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…Water can be rapidly supercooled to -43 degC (230 degK)the upper limit to superconducting Tc according to the present theoryor lower by confining water at nanoscale, e.g. in nanotubes 13. Recent x-ray studies of water supercooled to -15 degC in a quartz capillary have revealed the presence of pentagonal dodecahedral and other pentagonal water clathrate nanoclusters similar to those shown in Figs.…”
supporting
confidence: 68%
“…14 Therefore, it is expected that this trend would continue at even lower temperatures in a nanoscale environment. Pentagonal water clusters have been shown to be present in nanotubes13 and proteins near hydrophobic amino acids,15 where the hydrophobicity promotes the pentagonal clustering of water molecules. THz vibrations of water nanoclusters have been argued to be key to biomolecular function such as protein folding.…”
mentioning
confidence: 99%
“…The detailed analysis of this region is hampered by the complicated tube's structure and overlapping spectral lines. Even the deconvolution of this region into separate lines provides little information about the tube's structure, in spite of the partial lines assignment was performed recently …”
Section: Resultsmentioning
confidence: 99%
“…Even the deconvolution of this region into separate lines provides little information about the tube's structure, in spite of the partial lines assignment was performed recently. [35,43] Nevertheless, a lot of important information about the crystal structure and its behavior can be obtained from this region using an integrated approach based on the calculation of the effective frequency of the nanotubes' lattice vibrations. [41] Such frequency allows characterizing structural modifications and phase transitions in the tubes under the action of external forces.…”
Section: Analysis Of Lattice Vibrationsmentioning
confidence: 99%
“…Figure 3 represents the full Raman spectra at 14 and 345 K. The spectrum can be subdivided into three distinct regions, corresponding to the vibrations of constituting structural elements: (i) 10-280 cm −1 that is due to lattice vibrations, (ii) 280-1800 cm −1 vibrations of molecules' functional groups: lines at 1002 and 1032 cm −1 due to phenyl rings vibration, (iii) 2800-3350 cm −1 is a region of C−H, and N−H vibrational modes ( Figure 3). [21][22][23][24][25][26][27][28], and the interpretation of vibrations is also included. Table 1.…”
Section: Resultsmentioning
confidence: 99%